Determinants of the rate of return on capital in German corporations 1961 - 1975 - Reinhart Schmidt; Enno Langfeldt (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1977)
In the past years several researchers have called attention to the decline of the rate of return on capital. The difference of these investigations is based on the following items: 1. the country for which the investigation is carried out; 2. the period of time covered by the investigation; 3. the computation of nominal or real rates of return; 4. the reference to equity or total capital and to return before taxes or after taxes; 5. the derivation of the results from macroeconomic data or firm data. A decline of the rate of return on capital has been stated by Nordhaus (7) for the United States from 1948 to 1973, by King (4) for the United Kingdom from 1956 to 1973, and by Albach, Geisen, and Scholten (2) for the Federal Republic of Germany from 1960 to 1974 …
Keywords: 650